In what terms and at what cost resilient? 'Unregulated flexibilization' in regional 'troubled waters'. Issue 1 (2nd January 2020) - Gialis, Stelios; Paitaridis, Dimitris; Seretis, Stergios; Ioannides, Alexis; Underthun, Anders
ABSTRACT: This paper sheds light on the debate on regional resilience to crisis in Greece, a country long suffering from insufficient planning mechanisms and recently hit by a severe economic crisis. In the paper, we discuss the spatialities of employment flexibilization vis-à-vis the devaluation of regional productive structures between 2005 and 2016. The paper critically builds on previous accounts of regional resilience, but also seeks to develop the concept through engaging in: (i) how different employment patterns, namely part-time work, present a powerful adaptive mechanism that is related to path-dependent regional production profiles; and (ii) why regions with less favourable pre-crisis production structures and anaemic growth seem to have been less affected by recession and may witness a faster recovery in its aftermath. The paper adopts a multi-layered methodology, using a variety of measures, offering an empirically grounded theorization of contemporary labour market changes within the Southern EU. The results indicate some key reasons for radically reformulating established regulatory and planning practices in order to promote a pattern of resilience that is more friendly to good and well-paid jobs. A prerequisite for the latter is the promotion of territorially cohesive strategies that reduce regional disparities and harness 'unregulated flexibilization'.